2018
DOI: 10.4314/jab.v119i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation et gestion des pesticides en cultures maraîchères : cas de la zone de Nkolo dans la province du Kongo Central, République démocratique du Congo

Abstract: Objectives: Pesticides are systematically applied in vegetable crops at Nkolo (in Kongo Central province in the western DR Congo) in order to provide crop protection and improve the yield. This study aimed at assessing the knowledges and practices of gardeners in relation to of pesticides use. Methodology and Results : Forty-six gardeners were interviewed. The questionnaire focused on the pesticides types, solution procedures, application rate and frequency, gardener protective equipment, and the pre-harvest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 1 publication
2
8
0
5
Order By: Relevance
“…In this study, all the market gardeners were male. This result is similar to that found by two other studies, which found 93.47% and 98.3%, respectively [8,9]. This high proportion of men could be explained by the fact that market gardening is an activity purely dedicated to men.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, all the market gardeners were male. This result is similar to that found by two other studies, which found 93.47% and 98.3%, respectively [8,9]. This high proportion of men could be explained by the fact that market gardening is an activity purely dedicated to men.…”
Section: Discussionsupporting
confidence: 92%
“…A cause de l'insuffisance de la protection lors des traitements, les producteurs ont été plus victimes d'intoxications directes (par inhalation, par contact cutané ou oculaire) avec les pesticides (90%). Ces résultats corroborent avec les résultats de Muliele et al (2017) et Ngameni Tchamadeu et al (2017 sur les risques sanitaires encourus par les producteurs en raison des mauvaises conditions de gestion des pesticides.…”
Section: Discussionunclassified
“…Data collection was carried out through a questionnaire. The questionnaire was established with reference to that described by Muliele et al (2017), followed by some additions from the…”
Section: Methodsmentioning
confidence: 99%